Pandemic potential of H7N9 influenza viruses - Watanabe, Tokiko (Trends Microbiol, 2014)
Avian influenza viruses rarely infect humans, but the recently emerged avian H7N9 influenza viruses have caused sporadic infections in humans in China, resulting in 440 confirmed cases with 122 fatalities as of May 16, 2014. In addition, epidemiologic surveys suggest that there have been asymptomatic or mild human infections with H7N9 viruses. These viruses replicate efficiently in mammals, show limited transmissibility in ferrets and guinea pigs, and possess mammalian-adapting amino acid changes that likely contribute to their ability to infect mammals. Here, we summarize the characteristic features of the novel H7N9 viruses and assess their pandemic potential.